THE EFFECT OF POSTER-BASED ICE BREAKING ON STUDENTS’ LEARNING OUTCOMES IN SCIENCE SUBJECTS FOR GRADE IV AT MI NW SURABAYA IN THE 2024/2025 ACADEMIC YEAR - Ahmad Izzuddin; Haslinda (Formad English Foundation NTB Jakarta, 2025)
This study investigated the effect of poster-based ice-breaking activities on students’ learning outcomes in science subjects for Grade IV at MI NW Surabaya in the 2024/2025 academic year. The research aimed to determine whether implementing ice-breaking techniques using poster media could significantly enhance students' understanding and performance in science. A quantitative approach was employed, utilizing a quasi-experimental design with a post-test-only control group structure. Thirty Grade IV students were randomly assigned to experimental and control groups. The experimental group received poster-based ice-breaking interventions, while the control group underwent conventional learning. Data were collected through tests, observations, and documentation. Instrument validity and reliability were confirmed through point-biserial correlation and Cronbach's alpha analysis. Statistical analysis included normality, homogeneity, and t-tests. The findings revealed a significant difference between the experimental and control groups, with the experimental group achieving higher post-test scores. The results suggest that poster-based ice-breaking activities positively impact students’ science learning outcomes. This study highlights the potential of integrating creative media with interactive techniques to foster a more engaging and effective learning environment in science education for elementary students.